Associação dos níveis de atividade física com indicadores socioeconomicos, de obesidade e de aptidão física em adultos - Michelin, Edilaine [UNESP]; Corrente, José Eduardo [UNESP]; Burini, Roberto Carlos [UNESP] (My University, 2010)
With the purpose to investigate the association of demographics, socioeconomics, obesity and physical fi tness indicators on physical activity levels (PALs), retrospective data concerning 708 individuals (53.9±10.9 years) clinically tried for the lifestyle change program in clubs (LSCP) and Family Health Strategy (FHS), both ethically qualified in spontaneous demand, were assessed. PALs were assessed by long IPAQ forms (version 8), trunk flexibility by the sit-andreach test and handgrip strength (HGS) by dynamometry. The body mass index (BMI) and abdominal circumference (AC) were classified according to the World Health Organization. The groups were compared by Student’s t test, chi-square and logistic regression model fitting with p<0.05. FHS showed lower education levels (90.3% had completed primary school) and family income (59.2% <2 minimum salaries), worse perceptions of health conditions (66.3%), flexibility (76.6%), and handgrip strength (47.6%). However, 36.2% of FHS showed high PAL, with moderate activities at work and during leisure, such transportation, household chores, and leisurely walks differed level cited. Association of PALs with age, health conditions and handgrip strength was observed only in FHS. Individuals with optimal and good handgrip strength, males and with better perception of health conditions tended to present high, moderate and low PALs, respectively. Although the percentages for overweight and abdominal adiposity were high, moderate and high PALs predominated in both groups. Results suggest that everyday physical activities are insufficient for maintaining healthy body composition and physical fitness.

Objetivando investigar a associação de indicadores demográficos, socioeconômicos, de obesidade e de aptidão física com níveis de atividade física foram levantados dados retrospectivos de 708 indivíduos (53,9±10,9 anos) triados clinicamente para programa de mudança do estilo de vida em clubes urbanos e em Estratégia Saúde da Família (ESF), ambos eticamente habilitados em demanda espontânea. Apurou-se nível de atividade física (NAF-IPAQ-longo-versão 8), flexibilidade do tronco (sentar-e-alcançar) e força de preensão manual (dinamometria). Índice de massa corporal (IMC) e circunferência abdominal (CA) foram classificados de acordo com a Organização Mundial da Saúde. Comparou-se os grupos pelo teste t de Student, qui-quadrado e ajuste de modelo de regressão logística com p<0,05. A ESF apresentou menores escolaridade (90,3% até 1° grau completo) e renda familiar (59,2% <2 salários mínimos), piores percepção de saúde (66,3%), fl exibilidade (76,6%) e força de preensão manual (47,6%). Entretanto, 36,2% da ESF apresentaram NAF alto, com as atividades moderadas no trabalho e lazer, como meio de transporte, tarefas domésticas e caminhadas no lazer diferenciando tal NAF. Observou-se associação dos NAF com idade, estado de saúde e força de preensão manual somente na ESF. Indivíduos com força de preensão manual ótima e boa, homens e melhor percepção de saúde tenderam a apresentar, respectivamente, NAF alto, moderado e baixo. Embora elevados os percentuais de excesso de peso e adiposidade abdominal predominaram os NAF moderado e alto em ambos os grupos. Os resultados sugerem que as atividades físicas cotidianas são insuficientes para manutenção da composição corporal e da aptidão física em condições saudáveis.
Physical activity levels associated with socioeconomics, obesity and physical fitness indicators in adults
Keywords: Physical fitness; Lifestyle; Health; Questionnaire; Aptidão física; Estilo de vida; Saúde; Questionário